2006
DOI: 10.1111/j.1365-2036.2006.03107.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact on adherence and sustained virological response of psychiatric side effects during peginterferon and ribavirin therapy for chronic hepatitis C

Abstract: SUMMARY BackgroundThe psychiatric side effects of interferon, often responsible for dose reduction or treatment discontinuation, represent a major limitation in the treatment of chronic hepatitis C (CHC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 39 publications
3
36
1
1
Order By: Relevance
“…In our study, nearly 45% of the depression/anxiety disorders appeared in the first month and nearly 65% appeared in the first three months of the Peg-IFN treatment. Likewise in the study of Martin-Santos et al [13], half of the depression and anxiety syndromes appeared in the first month and more than 90% in the first 4 months, and in the study of Castera et al [12], mood disorders associated with Peg-IFN treatment emerged mostly (87%) in the first 12 weeks of 24 weeks of follow-up of patients with hepatitis C [12,13]. This shows that it is important to be alert for depressive symptoms especially in the first 3-4 months of the Peg-IFN treatment.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In our study, nearly 45% of the depression/anxiety disorders appeared in the first month and nearly 65% appeared in the first three months of the Peg-IFN treatment. Likewise in the study of Martin-Santos et al [13], half of the depression and anxiety syndromes appeared in the first month and more than 90% in the first 4 months, and in the study of Castera et al [12], mood disorders associated with Peg-IFN treatment emerged mostly (87%) in the first 12 weeks of 24 weeks of follow-up of patients with hepatitis C [12,13]. This shows that it is important to be alert for depressive symptoms especially in the first 3-4 months of the Peg-IFN treatment.…”
Section: Discussionmentioning
confidence: 74%
“…It is supposed that the central role is played by the interaction between the endocrine system, the immune system, the serotoninergic system, and the opioid receptors [4]. Although untreated depression is a major contributor to dosage reduction or premature discontinuation of the IFN treatment, it is found that depressive symptoms among patients undergoing hepatitis C virus (HCV) treatment are commonly overlooked by routine clinical interviews [9,12]. In addition to depression, anxiety disorders are shown to affect adherence to Peg-IFN treatment in patients with hepatitis C [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression and mental health issues prevail in the HCV population, represent barriers to treatment with combination therapy, and negatively influence adherence [21,22]. However, numerous studies have shown successful treatment of HCV in patients with depressive symptoms and/or mental health illnesses [23][24][25][26][27].…”
Section: Depression and Adherencementioning
confidence: 99%
“…However, 10%–40% additionally develop a full depressive disorder syndrome that can include suicidal ideation, amotivation, social withdrawal, guilt, anhedonia, irritability, anxiety, and crying (28). Untreated depression is a major contributor to dosage reductions or treatment discontinuations and consequent risk for viral relapse (911). Additionally, many patients with hepatitis C already have preexisting mental health disorders (12) that often go unrecognized (13).…”
Section: Newly Emergent Depression During Ifn-α Therapymentioning
confidence: 99%